The Flying Platform – A testbed for ducted fan actuation and control design. (April 2017) - Muehlebach, Michael; D'Andrea, Raffaello
Abstract: This article discusses the design of an unmanned aerial vehicle whose purpose is to study the use of electric ducted fans as control and propulsion system. Thrust vectoring is essential for stabilizing the vehicle. We present measurement results characterizing the thrust vectoring capabilities of the propulsion system (both statically and dynamically), discuss a first-principle model describing the behavior of the flying machine, and analyze and quantify the controllability about hover. The first-principle model is subsequently used for a cascaded control design, which is shown to work reliably in practice. Furthermore, system identification results are discussed and used to extended the model. The resulting augmented model is shown to match the measured frequency response function.